Altered distribution and function of splenic innate lymphoid cells in adult chronic immune thrombocytopenia. (September 2018) - Audia, Sylvain; Moulinet, Thomas; Ciudad-Bonté, Marion; Samson, Maxime; Facy, Olivier; Ortega-Deballon, Pablo; Saas, Philippe; Bonnotte, Bernard
Abstract: Innate lymphoid cells (ILCs) have been characterized as innate immune cells capable to modulate the immune response in the mucosae. Human ILCs have been rarely described in secondary lymphoid organs except in tonsils. Moreover, their function and phenotype in human secondary lymphoid organs during autoimmune diseases have never been studied. We took advantage of splenectomy as a treatment of immune thrombocytopenia (ITP) to describe and compare splenic ILC from 18 ITP patients to 11 controls. We first confirmed that ILC3 represented the most abundant ILC subset in human non-inflamed spleens, accounting for 90% of total ILC, and that they were mostly constituted of NKp44 - cells. On the contrary, proportions of ILC1 and ILC2 in spleens were lower than in blood. Splenic IL-2- and IFN-γ-producing ILC1 were increased in ITP. While the frequencies of total splenic ILC3 were similar in the two groups, splenic GM-CSF-producing ILC3 were increased in ITP. This is the first description of human ILC in a major secondary lymphoid organ during an autoimmune disease, ITP. We observed an expansion of splenic ILC1 that could participate to the Th1 skewing, while the increased production of GM-CSF by splenic ILC3 could stimulate splenic macrophages which play a key role in ITP pathophysiology. Highlights: IL-2- and IFNγ-producing splenic ILC1 are increased in ITP. GM-CSF-producing splenic ILC3 are increased in ITP. These results argue for a role for ILC in ITP pathogenesis, notably, such modifications could contribute to the initiation and/or the maintenance of the adaptive autoimmune response.